Ethanol sensors fabricated from PdO/WO3nanorods - Sathukarn Kabcum (2018)
© 2018, Chiang Mai University. All rights reserved. In this work, ethanol sensing films were prepared by spin-coating of PdO/WO3nanorods pasted onto Al2O3substrates interdigitated with Au electrodes and tested towards 50-2000 ppm C2H5OH at different operating temperatures ranging from 150-350 °C. It was found that the C2H5OH responses of PdO-loaded WO3sensors monotonically increased with increasing operating temperature to 350 °C and increased greatly with increasing PdO-loading level up to 1.0 wt%. In particular, the optimal 1.0 wt% PdO-loaded sensor exhibited an ultra-high response of 1.52 ×104to 2000 ppm C2H5OH at 350 °C with a short response time of ∼3 s. In addition, PdO-loaded WO3sensing films displayed high ethanol selectivity against CO, NO2, NH3and H2S. Therefore, PdO-loaded WO3nanorods sensors prepared by the precipitation and impregnation methods are promising for highly sensitive and selective for ethanol sensing.